Perforated Jejunoileal Tuberculosis in free Peritoneum - Campos Pierri, Néstor; Acosta y Lara, Armando; Sautto, Néstor; Revetria, Ricardo; Fontes, Luis (Cirugía del Uruguay, 1981)
Description of a case of tubercul'ose perforated ulcer of small intestine in free peritoneum, treated surgically with good evolution.